2012
DOI: 10.3346/jkms.2012.27.10.1241
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic eIF4E-binding Protein 1 (eIF4E-BP1) mRNA Is Upregulated by Neuronal Activation

Abstract: Long-term synaptic plasticity requires addition of new proteins at the synaptic site. The local protein synthesis at subsynaptic sites confers advantageous mechanisms that would regulate the protein composition in local domains on a moment-by-moment basis. However, our information on the identities of 'dendritic' mRNAs is very limited. In this study we investigated the expression of the protein and mRNA for eukaryotic translation initiation factor 4E (eIF4E)-binding protein 1 (4EBP1) in cultured rat hippocampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Fatty acid binding proteins (FABPs) play a critical role as their cellular shuttles [ 26 ]. EIF4E is a signaling protein that regulates cell growth and proliferation, and can be activated in dendrites due to the activation of neurons [ 27 ]. MSRB3 is involved in protein–protein interactions, including protein folding, neuroprotection, and cell survival [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid binding proteins (FABPs) play a critical role as their cellular shuttles [ 26 ]. EIF4E is a signaling protein that regulates cell growth and proliferation, and can be activated in dendrites due to the activation of neurons [ 27 ]. MSRB3 is involved in protein–protein interactions, including protein folding, neuroprotection, and cell survival [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 4EBP1 protein and its mRNA are upregulated and transported to dendritic domains in RNA granules upon neuronal activation 33 . Local protein synthesis in axons is a critical component of synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in accordance with the previous report. DIV 16 hippocampal neurons expressed eIF4E throughout dendrites but not in the nucleus, while eIF4EBP1 was distributed throughout the neuron with highest expression in the nucleus [9]. There were many eIF4E, eIF4EBP1 and PSD95 puncta in the dendrites of DIV 20 neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High resolution confocal microscopy and detergent extraction experiments showed that the eIF4E, eIF4G, eIF5, eIF5A and eIF6 were localized to the postsynaptic sites in association with the postsynaptic density (PSD) [3]. Furthermore, eIF4E and eIF4EBP1 mRNAs are localized, and upregulated by neuronal stimulation, in dendrites of cultured rat hippocampal neurons [9,11].Neurons undergo complex morphological development. Dendrites will initially outgrow, followed by extensive branching and lengthening during dendrogenic stage.…”
mentioning
confidence: 99%